P447 Early predictors of the need for surgery in patients with acute severe ulcerative colitis: results of the prospective, observational, international ESCP MASC study. (30th January 2023) - Frasson, M; Pinkney, T; Gisbert, J P; Rodriguez-Lago, I; Blackwell, S; Gecse, K B; Buskens, C J; Knowles, C; Zmora, O; Brookes, M; Fiorino, G; Nos, P; et al.
Abstract: Background: Acute severe ulcerative colitis (ASUC) is a potentially life-threatening condition, requiring immediate hospitalization. Delayed colectomy is associated with increased risk of post-operative complications. This study aimed to identify early predictors of failure to medical treatment and need for colectomy in patients with ASUC. Methods: The Management of Acute Severe ulcerative Colitis (MASC) Audit was an international, prospective, observational, cohort study, in which data on consecutive patients hospitalised for ASUC at participating units over a minimum 6-month period in 2019-20 were collated. The need for surgery during the first 90 days after admission was the primary outcome of the study. Data on all consecutive patients admitted for ASUC at the participating units were prospectively entered in an online secure database. A multivariate regression logistic model was developed to identify early predictors of colectomy. The study was developed by a multidisciplinary panel of collaborators, including gastroenterologists, surgeons, and patients, and it was discussed at the 5th IBD National Study Group of the ECCO. The study was led by the European Society of Coloproctology (https://tinyurl.com/vfwmahva ). Results: Out of 706 patients included in the database, data from 699 patients from 123 centres located in 32 different countries were included in the analysed (Figure 1). Median age was 38 (IQR, 28-54) years; 265 (38%) patients had a previous admission for UC and 39 (6%) had undergone previous appendicectomy. At admission, 13% patients were on monotherapy with 5-ASA, 19% systemic steroids, and 19% biologic agents. Within 90 days after admission, 258 (37%) patients required surgery: 29.7% received second-line and 1.4% received third-line medical therapy. Overall mortality was 1%. Among those patients requiring surgery, postoperative morbidity was 36% (Table 1). Being a current smoker (OR 2.6, 95%CI 1.2-6.0), previous appendicectomy (OR 6.3, 95%CI 2.1-20.0), previous admission for UC (OR 2.6, 95%CI 1.5-4.4), admission to a surgical unit (OR 9.8, 95%CI 4.3-22.5), type of pre-admission therapy and C-reactive protein levels on day 3 after admission (OR 1.01 per mg/L, 95%CI 1.00-1.01, ROC curve in Figure 2) were independent predictors of failed medical treatment. Conclusion: Mortality for ASUC did not exceed 1% in this series. Patients who smoked or had previous appendicectomy were at increased risk of medical failure. These factors seem to challenge the current knowledge on UC course, and the findings merit further investigation. C-reactive protein on day 3 after admission was identified as a potential marker to predict the subsequent need for surgery.